2010
DOI: 10.4103/0253-7184.68998
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir-associated renal dysfunction in clinical practice: An observational cohort from western India

Abstract: Background:Tenofovir (TDF) is preferred nucleoside reverse transcriptase inhibitors (NRTI) for the treatment of human immunodeficiency virus infection because of its potency and safety. Renal toxicity with TDF use is low and comparable with other NRTI in clinical trials, but there are many case studies and small case series of renal dysfunction with TDF.Materials and Methods:This is an observational longitudinal cohort of patients started on a TDF-based regimen from January 2007 to April 2010. Patients were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 17 publications
(29 reference statements)
3
28
0
Order By: Relevance
“…Similarly, a 10 year follow-up cohort study of HIV-positive patients, reported that the quantified loss in eGFR attributable to Tenofovir was relatively modest after many years of exposure [12]. Since the majority of our patients had been on ART for more than 9 years, our failure to find an association between renal dysfunction and duration on Tenofovir containing ART can be explained by previous studies that reported that the loss in eGFR attributable to Tenofovir seemed to occur during the first years of exposure between 0.5 and 31.2 months and stabilized after that [16, 17, 2528]. Post marketing studies reported advanced age, low body weight, comorbidities such as diabetes mellitus, hypertension, as some of the risk factors for Tenofovir induced renal dysfunction [27, 29, 30].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Similarly, a 10 year follow-up cohort study of HIV-positive patients, reported that the quantified loss in eGFR attributable to Tenofovir was relatively modest after many years of exposure [12]. Since the majority of our patients had been on ART for more than 9 years, our failure to find an association between renal dysfunction and duration on Tenofovir containing ART can be explained by previous studies that reported that the loss in eGFR attributable to Tenofovir seemed to occur during the first years of exposure between 0.5 and 31.2 months and stabilized after that [16, 17, 2528]. Post marketing studies reported advanced age, low body weight, comorbidities such as diabetes mellitus, hypertension, as some of the risk factors for Tenofovir induced renal dysfunction [27, 29, 30].…”
Section: Discussionmentioning
confidence: 78%
“…In a Canadian cohort, renal dysfunction was observed in the early years of exposure to Tenofovir but the risk remained minimal beyond 6 years [12]. The median time to develop Tenofovir renal dysfunction was estimated at 154 (15–935) days in a clinical practice in western India [16]. Others have reported that tubular dysfunction or renal failure was diagnosed 6.89 ± 5.51 months after starting Tenofovir [17].…”
Section: Introductionmentioning
confidence: 99%
“…The possible risk factors associated in the study group was CD4>200 (P=0.003); further details on risk factors were shown in table 2. [15]. Patients with raise in serum creatinine were largely asymptomatic, however patient with acute renal failure had presented with weakness, body pain and vomiting.…”
Section: Resultsmentioning
confidence: 99%
“…TDF currently is a recommended first-line agent in combination with other antiretroviral drugs for HIV management in Zambia. This is because of its favorable pharmacokinetic profile, good antiviral potency and high tolerability [3,7]. The high number of renal dysfunction cases missed at initiation and follow up suggests that screening of patients prior to initiation is rare.…”
Section: Discussionmentioning
confidence: 99%
“…TDF is an oral prodrug of tenofovir, a nucleotide reverse transcriptase inhibitor (NRTIs) that has been indicated for use from many randomized trials [1,[4][5][6] because of its favorable pharmacokinetic profile, availability as a once-daily fixed dose, good antiviral potency and high tolerability [3,7]. TDF has been considered safe and associated with fewer side-effects in many clinical trials [4,5,8].…”
Section: Introductionmentioning
confidence: 99%